Decannulation in patients undergoing head and neck cancer surgery: Rapid review - Ana Inês Frade; José Moreira; Lucinda Pires; Marta Duarte; Tiago Cunha; Susana Miguel (Associação de Enfermagem Oncológica Portuguesa, 2023)
Introduction: Tracheotomy is commonly used in patients with head and neck cancer undergoing major surgery. Purpose: Aims to identify the nursing interventions in the safe decannulation process in patients undergoing head and neck cancer surgery. Methods: Rapid review on MEDLINE and CIHNAL, January 2023. Results: Seven studies met the inclusion criteria. The nursing intervention was grouped into before decannulation, during the decannulation process and after the decannulation. Conclusion: The literature review shows the need for a structured nursing process supporting safe decannulation. The team must ensure which was the criteria for elective tracheotomy were resolved and that no anesthetic or surgical procedure is foreseen shortly. These are essential factors associated with the state of consciousness, deflated tube' cuff and tube cap tolerated before decannulation. The literature highlights the need for experienced teams, including nurses, to ensure the safe decannulation process.